Analisis Efektivitas Pelaporan Tandan Buah Segar Menggunakan Near Field Communication (NFC) di PT Nusa Pusaka Kencana Kebun Bahilang - Suhar Syaputra; Tuty Ningsih (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The digitization of production reporting systems is a crucial step in improving the effectiveness and accuracy of data in the oil palm plantation industry. This study aims to analyze the effectiveness of using Near Field Communication (NFC) technology in reporting Fresh Fruit Bunches (FFB) at PT Nusa Pusaka Kencana’s Bahilang Plantation. Prior to the implementation of NFC, the reporting process was conducted manually, which took longer and was prone to recording errors. The research method used was quantitative descriptive analysis with a saturated sampling technique involving 5 respondents, consisting of harvest supervisors, truck drivers, and scale operators. Data were collected through observation, interviews, documentation, and company records. Data analysis was performed using the Shapiro-Wilk normality test and the paired t-test. The results showed that the average reporting time before NFC implementation was 36.98 seconds, while after implementation it decreased to 29.97 seconds, resulting in an average time savings of 7.01 seconds per transaction. The results of the paired t-test showed that the calculated t-value of 20.851 was greater than the critical t-value of 2.0452, with a significance level of 0.000 < 0.05, indicating a significant difference between manual reporting and reporting using NFC. Based on the research findings, it can be concluded that NFC technology has proven effective in improving the speed and accuracy of fresh fruit bunch (FFB) reporting at PT Nusa Pusaka Kencana’s Bahilang Plantation.